Prothrombin-Sepharose-Purified Factor V and Its Role in Prothrombin Conversion - T.C ONG (Universitas Gadjah Mada, 1986)
Bovine Factor V isolated by the method of Esnouf and Jobin (1967) has been further purified by affiniy chromotgraphy through prothrombin-sepharose. Factor V bound quantitative to the prothrombin-sepharose column. There was a 2-fold increase in the average specific activity (260.000 units/mg protein) of the Factor V recovered. Recovery of total Factor V activity and total protein was about 95% and 90% respectively.